PENGAWASAN PUBLIK DIGITAL : EVALUASI STRATEGIS SISTEM INFORMASI MANAJEMEN PENYELESAIAN LAPORAN DI OMBUDSMAN REPUBLIK INDONESIA - Sabtelasari, Rani; Wahyugi, Dodi (SINERGI : Jurnal Riset Ilmiah, 2025)
ABSTRACT The government digital transformation in Indonesia requires an information system that supports data integration, transparent governance, and evidence-based decision-making. The Indonesian Ombudsman developed the Report Settlement Management Information System (SIMPeL) as part of an effort to strengthen the institution's role in promoting the digitalization of public service oversight. This study aims to evaluate the alignment of SIMPeL with the principles of digital governance, identify technical and institutional challenges, and formulate strategic development directions. The methods employed are a literature review and policy analysis, with a policy foresight approach. The results show that although SIMPeL has initial integration with SP4N-LAPOR! and a strong regulatory foundation, gaps remain in interoperability, metadata standardization, and the use of data analytics. Strategic strengthening directions include the development of open APIs, metadata standardization, hybrid cloud utilization, the establishment of a Data and Information Center, the application of Artificial Intelligence for predictive analytics, and increasing employee digital literacy. With these steps, SIMPeL is expected to evolve from a mere case management system into a modern, adaptive decision support system that supports national bureaucratic reform.